1987
DOI: 10.1128/jvi.61.4.945-954.1987
|View full text |Cite
|
Sign up to set email alerts
|

A bicistronic Epstein-Barr virus mRNA encodes two nuclear proteins in latently infected, growth-transformed lymphocytes

Abstract: EBNA2 is a nuclear protein expressed in all cells latently infected with and growth transformed by Epstein-Barr virus (EBV) infection (K. Hennessy and E. Kieff, Science 227:1230-1240, 1985). The nucleotide sequence of the EBNA2 mRNA (J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
40
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(42 citation statements)
references
References 71 publications
2
40
0
Order By: Relevance
“…It was suggested that in such cases, eucaryotic ribosomes are capable of terminationreinitiation reactions, thus allowing for the expression of downstream ORFs (see, e.g., references 20 and 21). Consistent with this, the polypeptide products encoded by the upstream minicistrons on several bicistronic mRNAs have been detected in vivo (7,10,34) and in vitro (4). The presence of upstream minicistrons generally acts to decrease the expression of the downstream major ORF (9,10,18,21,29), possibly because not all terminating ribosomes become competent for reinitiation.…”
mentioning
confidence: 63%
“…It was suggested that in such cases, eucaryotic ribosomes are capable of terminationreinitiation reactions, thus allowing for the expression of downstream ORFs (see, e.g., references 20 and 21). Consistent with this, the polypeptide products encoded by the upstream minicistrons on several bicistronic mRNAs have been detected in vivo (7,10,34) and in vitro (4). The presence of upstream minicistrons generally acts to decrease the expression of the downstream major ORF (9,10,18,21,29), possibly because not all terminating ribosomes become competent for reinitiation.…”
mentioning
confidence: 63%
“…Again, the broader antigenic response to EBV compared with KSHV is striking. The W1 exon of EBV BamHI-W encodes 22 amino acids that form part of the EBNA-LP protein [33,34]. The protein encoded by the entire EBV BamHI-W ORF (BWRF1) and the EBNA-LP protein were both printed on the array.…”
Section: Comparison Of Plasma From Hiv-positive Patients With Kshv-asmentioning
confidence: 99%
“…hsp72/hsc73 may mediate the previously observed interaction between EBNA-LP and the retinoblastoma protein or p53.The Epstein-Barr virus (EBV) nuclear antigen leader protein (EBNA-LP) plays a critical role in EBV-induced transformation (4,9). EBNA-LP mRNA is composed of repeating 22and 44-amino-acid-encoding exons (the W repeats) and two unique exons (Y1 and Y2) encoding the C-terminal 45 amino acids (15,21). EBV recombinants with a 45-amino-acid Cterminal truncated EBNA-LP due to a deletion of the Y1 and Y2 exons yielded 10-to 20-fold-fewer cell colonies in a fibroblast feeder layer soft agar assay than virus stocks derived from recombinant EBVs expressing an intact EBNA-LP (4).…”
mentioning
confidence: 99%